IDENTIFICATION OF PESTICIDE COMPOUNDS OF CYNODON DACTYLON BY GC-MS ANALYSIS - P. JEGAJEEVANRAM; N.M.I.ALHAJI; S. KUMARAVEL (International Journal of Pharma and Bio Sciences, 2014)
Cynodon dactylon (L.) Pers. (Family–Poaceae), is traditionally used for curing different aliments like wound healing. In the present investigation, Gas Chromatography Mass Spectrometry (GC-MS) analyses of C. dactylon leaves were carried out to evaluate chemical composition which could be useful in future experimental studies. This analysis revealed that the leaves contain pesticide compounds like 2,6,10,14,18,22-Tetracosahexaene, 2,6,10,15,19,23-hexamethyl- with the relative percentage of 48.36 % of the total compounds in total ion chromatogram. In conclusion, the identification of this compound will help the researchers in the development of several treatment formulations based on this plant.